2012
DOI: 10.1155/2012/235971
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of SnO2Film Deposited by Magnetron Sputtering

Abstract: Tin oxide SnO 2 films were prepared by RF magnetron sputtering. The effects of oxygen partial pressure percentage on the SnO 2 property have been investigated to obtain relatively high-resistivity SnO 2 films which could be used as buffer layers to optimize the performance of CdTe/CdS solar cells. The oxygen partial pressure percentage varied in the range of 1%∼10%. The results show that the introduction of oxygen would suppress the deposition and growth of SnO 2 films. Electrical measurement suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…where α is the absorption coefficient, which is related to the thickness of the film, hυ is defined as photon energy, A is a constant, and the value of n depends on the energy-band structure of the material. For direct energy-band semiconductor materials, such as SnO 2 , n is 0.5 [16]. The obtained E g was 4.33 eV for TEC 10, agreeing well with the former result [17].…”
Section: Optical Propertiessupporting
confidence: 87%
“…where α is the absorption coefficient, which is related to the thickness of the film, hυ is defined as photon energy, A is a constant, and the value of n depends on the energy-band structure of the material. For direct energy-band semiconductor materials, such as SnO 2 , n is 0.5 [16]. The obtained E g was 4.33 eV for TEC 10, agreeing well with the former result [17].…”
Section: Optical Propertiessupporting
confidence: 87%
“…Herewith, our SnO 2 thin films enqueue themselves into the known spectrum of resistivities reported for SnO 2 thin films. At room temperature, SnO 2 thin films manufactured by atomic layer deposition (ALD), sputtering, spray pyrolysis, EBE, and CVD exhibited resistivities of ≈2 × 10 −4 , 2.5 × 10 −5 , 2 × 10 −5 , 5 × 10 −5 , 5 × 10 −4 , and 4.5 × 10 −4 Ω m, respectively . The observable variation in the literature is related to different microstructures at different deposition temperatures and more importantly different stoichiometries that can be obtained with the different deposition techniques.…”
Section: Resultsmentioning
confidence: 99%
“…They found when oxygen pressure was increase, resistivity of the film also reduces with its indicated in electrical measurement. In pure argon atmosphere SnO 2 films with resistivity was found 232 Wcm.Stedile et al [30] report was found magnetron sputtered SnO 2 films were submitted to thermal annealing and exposed to butane gas, its highly disordered. The SnO 2 films are modified under thermal processing and gas exposure, changing the oxygen vacancy concentration as could be observed in their experiment.…”
Section: B Synthesis and Characterization Of Snomentioning
confidence: 99%